Reading Comprehension Skills And Performance In Science Among High School Students In The Philippines - A. Imam, Ombra; Mastura, Maripaz Abas; Jamil, Hajri; Ismail, Zurida (Penerbit Universiti Sains Malaysia, 2014)
The research work was carried out among randomly selected 666 first year student-respondents from 18 identified public and private high schools in the Division of Cotabato City, Central Mindanao, Philippines. The six elements of reading comprehension skills, i.e., understanding vocabulary in context, identifying main idea, noting details, making inference, predicting outcomes, and drawing conclusion, and students’ performance in science from the two school types were described and correlated. A competency-based 50-item multiple choice achievement test for each of the reading comprehension and science learning areas was utilised as the research instrument. The test was developed based on the prescribed Table of Specifications (TOS) and aligned with learning competencies formulated under the Restructured Basic Education Curriculum (RBEC) of the Department of Education (DepEd). The study results showed that the overall students’ performance in reading comprehension and science was indexed at low mastery level. Generally, four out of six reading skills such as understanding vocabulary in context, noting details, predicting outcome, and making inference made up the overall reading skills that positively correlated with science performance of students although the strength of relationship was considered weak.